Anti-HMGB1 monoclonal antibody therapy for a wide range of CNS and PNS diseases - Masahiro Nishibori; Shuji Mori; Hideo K. Takahashi (Elsevier, 2019)
High mobility group box-1 (HMGB1), a representative damage associated-molecular pattern (DAMP), has been reported to be involved in many inflammatory diseases. Several drugs are thought to have potential to control the translocation and secretion of HMGB1, or to neutralize extracellular HMGB1 by binding to it. One of these drugs, anti-HMGB1 monoclonal antibody (mAb), is highly specific for HMGB1 and has been shown to be effective for the treatment of a wide range of CNS diseases when modeled in animals, including stroke, traumatic brain injury, Parkinson's disease, epilepsy and Alzheimer's disease. Thus, anti-HMGB1 mAb not only is useful for target validation but also has extensive potential for the treatment of the above-mentioned diseases. In this review, we summarize existing knowledge on the effects of anti-HMGB1 mAb on CNS and PNS diseases, the common features of translocation and secretion of HMGB1 and the functional roles of HMGB1 in these diseases. The existing literature suggests that anti-HMGB1 mAb therapy would be effective for a wide range of CNS and PNS diseases. Keywords: High mobility group box-1 (HMGB1), Monoclonal antibody (mAb), DAMP, Neuroinflammation, Stroke, TBI, Epilepsy, Neuropathic pain